How alien species use cognition to discover, handle, taste, and adopt novel foods. (June 2022) - Griffin, Andrea S; Peneaux, Chloe; Machovsky-Capuska, Gabriel E; Guez, David
Abstract : Humans are translocating species beyond their native ranges increasingly fast. These translocations create a natural experiment to explore the role of cognition in invasiveness. Alien vertebrate species face many behavioral challenges upon introduction to novel environments. But here, we focus on how alien species might use cognition to find and adopt new foods. Cognitive processes are particularly well suited to this challenge, a prediction supported by large-scale comparative analyses of alien species' historical introductions. Here, we parse the steps involved in approaching, handling, tasting, and evaluating novel food sources and, for each one, describe which cognitive abilities are the most relevant. In bringing attention to the functional importance of innovative feeding both conceptually and empirically, synthesizing the cognitive processes involved, highlighting the current void of knowledge, and arguing that alien species are particularly well suited to controlled experimental cognitive studies, this piece scaffolds future experimental cognitive research.